2017
DOI: 10.1073/pnas.1713574114
|View full text |Cite
|
Sign up to set email alerts
|

MPSR1 is a cytoplasmic PQC E3 ligase for eliminating emergent misfolded proteins in Arabidopsis thaliana

Abstract: SignificanceThe essential roles of cytoplasmic E3 ligases in the protein quality control (PQC) pathways have been increasingly highlighted in yeast and animal studies. However, in plants, only CHIP E3 ligase has been characterized, while the knowledge of cytoplasmic PQC E3 ligases remains rudimentary. Misfolded Protein Sensing RING E3 ligase 1 (MPSR1), a self-regulatory sensor system that functions only in the occurrence of misfolded proteins, is an identified cytoplasmic PQC E3 ligase in plants that directly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(33 citation statements)
references
References 48 publications
0
33
0
Order By: Relevance
“…3D). To rule out the possibility that potential side effects of Tm treatment rather than the ER stress could lead to a cytosolic reduction, we adopted the L-proline analog azetidine-2-carboxylic acid (AZC), which causes ER stress by competing with D-proline for incorporation into newly synthesized proteins, causing protein misfolding (42). We used two concentrations of AZC and found that the AZC treatment also resulted in a cytosolic reduction of roGFP2 in a dosedependent manner compared with untreated conditions (SI Appendix, Fig.…”
Section: Resultsmentioning
confidence: 99%
“…3D). To rule out the possibility that potential side effects of Tm treatment rather than the ER stress could lead to a cytosolic reduction, we adopted the L-proline analog azetidine-2-carboxylic acid (AZC), which causes ER stress by competing with D-proline for incorporation into newly synthesized proteins, causing protein misfolding (42). We used two concentrations of AZC and found that the AZC treatment also resulted in a cytosolic reduction of roGFP2 in a dosedependent manner compared with untreated conditions (SI Appendix, Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Leaf protoplasts of 35S:GFP-TUB6 were transfected with the pBI221 empty vector or pBI221 harboring the 35S:29Flag-JUL1 construct. The in vivo co-IP assay using anti-GFP and anti-Flag antibodies was conducted as described previously (Kim et al, 2017). For in vitro pull-down assay, MBP, MBP-SPR1, and MBP-JUL1 were incubated with tubulin purified from porcine brain tissues (Cytoskeleton, Inc., Denver, CO, USA, http://cytoske leton.com) in the presence of amylose resin.…”
Section: Subcellular Localization In Vivo Co-ip and In Vitro Pulldomentioning
confidence: 99%
“…However, they are apparently not equally redundant, as overexpression of SNIPER2 exhibits distinct developmental defects while SNIPER1 overexpression is fully WT‐like in morphology. SNIPER2 (also named as MPSR1) was previously reported as a cytoplasmic chaperone‐independent protein quality control (PQC) E3 ligase for sensing and ubiquitinating misfolded proteins for their degradation (Kim et al , ). In addition, inverse correlation between MPSR1 and chaperone protein was observed for cytoplasmic protein quality control in response to proteotoxic stress (Kim et al , ).…”
Section: Discussionmentioning
confidence: 99%